2015
DOI: 10.1016/j.jacc.2015.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Outcomes of Surgical Treatment in Carcinoid Heart Disease

Abstract: Operative mortality associated with valve replacement surgery for CaHD has decreased. Symptomatic and survival benefit is noted in most patients when CaHD is managed by an experienced multidisciplinary team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 28 publications
2
101
5
1
Order By: Relevance
“…17,18 Without surgery, only 10% of the patients will survive after 2 years of onset of New York heart association (NYHA) functional class III and IV symptoms. 18 The optimal timing of surgery in relation to the signs and symptoms of severe valvular dysfunction has not been clearly defined. Further more, perioperative mortality for those undergoing valve replacement remains high.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Without surgery, only 10% of the patients will survive after 2 years of onset of New York heart association (NYHA) functional class III and IV symptoms. 18 The optimal timing of surgery in relation to the signs and symptoms of severe valvular dysfunction has not been clearly defined. Further more, perioperative mortality for those undergoing valve replacement remains high.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial decrease in mortality rates between the 2 study periods (28 vs. 6%, p = 0.004) was reported, which was attributed by the authors to changes in preoperative and intraoperative management, such as the use of aprotinin, shorter duration of cardio-pulmonary bypass and aortic cross-clamping, and increased implementation of PV replacement rather than valvotomy. In a recent study, Connolly et al [36] reported the short- and long-term outcomes of the largest case series (n = 195) of consecutive patients submitted to cardiac surgery for CHD treatment at the same center (Mayo Clinic, Rochester, N.Y., USA) over a 27-year period, between 1985 and 2012. Tricuspid, pulmonary, mitral, or aortic valve disease that warranted intervention was detected in 195, 157, 21, and 18 patients, respectively.…”
Section: Chd Treatmentmentioning
confidence: 99%
“…Among these, the most prominent seems to be the comparative efficacy and safety of the 2 types (bioprosthetic vs. mechanical) of prosthetic valves used. Although anecdotal reports have described premature degeneration of the implanted bioprosthetic valve (as early as 3 months postoperatively) and attributed the disorder to elevated 5-HIAA levels [46,47], more recent data have demonstrated the safety and longevity of bioprosthetic valves [36]. Furthermore, one must highlight the existence of a trend for increased survival among the patients who had received bioprosthetic versus mechanical valves in the same cohort.…”
Section: Current Trends and Unresolved Issuesmentioning
confidence: 99%
See 2 more Smart Citations